1.

3a + 7 = 28

2.

4b - 3 = 9

3a + 7 - 7 = 28 - 7 ... remove 7

4b - 3 + 3 = 9 + 3 ... remove 3

3a = 21

4b = 12

a = 7 ... divide by 3

b = 3 ... divide by 4

3.

c = 2

4.

x = − 5

5.

x = − 3

6.

x = 1

7.

y = − 1

8.

a = 2

9.

a = − 3

10.

7x + 12 = 2(3x - 7)

11.

3x = 8(x + 3) - 9

7x + 12 = 6x - 14 ... remove brackets

3x = 8x + 24 - 9 ... remove brackets

7x - 6x = - 14 - 12 ... gather like terms

3x - 8x = 24 - 9 ... gather like terms

x = − 26 ... simplify

x = − 3 ... simplify

12.

a = − 3

13.

b = 4

14.

c = 0,6

15.

m = 0,5